(untitled) (Journal Of Educational and Psychological Researches, 2024)
The research aims to identify the most important training needs for Arabic language teachers in private and public sector schools in the Sultanate of Oman, as well as measure the differences in training needs of Arabic language teachers regarding gender, school affiliation, and number of years of experience. The research adopted the descriptive-analytical method. The research sample consisted of 189 Arabic language school teachers in the Sultanate of Oman. The researcher developed a questionnaire for measuring the training needs based on Arabic language teachers’ perspectives, which included 60 items. The research concluded that the level of training needs in the total score of the questionnaire was medium, with a mean score of 3.32. Evaluation competencies came in first place, followed by educational competencies. The third place is occupied by the lesson implementation competencies. As for competencies in preparing for the lesson, they took the last place. There are statistically significant differences between male and female teachers in training needs in favor of male teachers. There are no statistically significant differences according to school affiliation and years of experience.